2009
DOI: 10.2116/analsci.25.1319
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Position Effect on Twisted intramolecular Charge Transfer of 1- and 2-anthracene aromatic Carboxamides as Chemosensors Based on Linear Polyether

Abstract: Bi-chromophoric compounds linked to linear polyether N, N′-[oxybis(3-oxapentamethyleneoxy-2-phenyl)]-bis(1-anthracenecarboxamide) (14) and its analogues (15, 24 and 25) were synthesized. Their photochemical properties and complexation actions were investigated in acetonitrile. These fluoroionophores have shown weak emissions in the absence of guest ions, resulting in a twisted intramolecular charge transfer (TICT) quenching process (off state) of an anthracene aromatic amide moiety. After the formation of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As a consequence, (11) exhibited a 50-70-fold increase in its fluorescence intensity by the addition of Ca 2+ , Sr 2+ or Ba 2+ ions. 42 This strategy, wherein complexation prevents TICT formation by imposing steric restriction, is also effective for the detection of neutral molecules such as surfactants. 43…”
Section: Sensing Microenvironmental Viscositymentioning
confidence: 99%
“…As a consequence, (11) exhibited a 50-70-fold increase in its fluorescence intensity by the addition of Ca 2+ , Sr 2+ or Ba 2+ ions. 42 This strategy, wherein complexation prevents TICT formation by imposing steric restriction, is also effective for the detection of neutral molecules such as surfactants. 43…”
Section: Sensing Microenvironmental Viscositymentioning
confidence: 99%
“…In model compounds, D and A are often linked by a single covalent bond such that photoexcitation of the system results in torsional motion about that bond as CT occurs. Indeed, many examples of twisted intramolecular CT (TICT) states have been studied. ,, In these cases, when the photoexcited D–A system relaxes from its local exciton (LE) state, CT is favored when the two π systems have large dihedral angles relative to one another, while conversely, maintaining planarity between the D and A π systems favors relaxation of the LE state, often via radiative decay by fluorescence. , TICT states have proven useful in developing optimized organic light-emitting diodes, high-efficiency organic photovoltaics, finely tuned aggregation-induced emission luminogens (AIEgens), , and techniques for sensing chemical species, microenvironmental viscosity, and environmental polarity . For example, Sunahara and co-workers took advantage of this architecture to develop a library of BODIPY-containing compounds exhibiting different degrees of TICT state formation to be utilized for solvent polarity sensing.…”
Section: Introductionmentioning
confidence: 99%
“…14 To address the problem described above, we introduced twisted intramolecular charge transfer (TICT) as a fluorescence-related switching mechanism. [15][16][17][18] The utilization of the TICT process enables fluorescence switching of a chemosensor by a degree of the steric barrier. It was reported that TICT was controlled by micellar aggregation 19 and the use of a viscous solvent.…”
Section: Introductionmentioning
confidence: 99%